119 Cluster-randomised controlled trial of a fire safety injury prevention briefing in children's centres. (1st September 2016) - Deave, Toity; Hawkins, Adrian; Hayes, Mike; Cooper, Nicola; Coupland, Carol; Majsak-Newman, Gosia; Goodenough, Trudy; McColl, Elaine; Reading, Richard; Kendrick, Denise
Abstract : Background: The UK has high mortality rates for fire-related deaths in children aged 0–14 years with steep social gradients. Interventions to promote fire safety practices can be effective in reducing the risk of fire-related injury. We therefore developed an evidence-based fire safety intervention comprising an Injury Prevention Briefing (IPB), training and facilitation for use in children's centres. Methods: A cluster randomised controlled trial, with integrated qualitative study, was conducted across four study sites in England involving children's centres in disadvantaged areas; participants were staff and families attending those centres. Centres were stratified by study site and randomised within strata to one of three arms: IPB plus facilitation (IPB+), IPB only, usual care. IPB+ centres received initial training and facilitation at months 1, 3, and 8. Data collected comprised baseline and 12 months parent- and staff-completed questionnaires, home safety activity logs and staff interviews. The primary outcome was the proportion of families with a home fire-escape plan. Treatment arms were compared by using multilevel models to account for clustering by centre. Results: 1112 parents at 36 CCs participated. There was no significant effect of the intervention on family possession of fire-escape plans (AOR IPB only vs. usual care: 0.93, 95% CI: 0.58, 1.49; AOR IPB+ vs. usual care 1.41, 95% CI: 0.91, 2.20). However, significantly more families in the intervention arms achieved more fire-escape planning behaviours (AOR IPB only vs. usual care: 2.56, 95% CI: 01.38, 4.76; AOR IPB+ vs. usual care 1.78, 95% CI: 1.01, 3.15). Conclusions: Our study demonstrated that children's centres can deliver an injury prevention intervention to families in disadvantaged communities and achieve changes in home safety behaviours.